Autism spectrum disorder prevalence in Italy: a nationwide study promoted by the Ministry of Health - Maria Luisa Scattoni; Laura Maria Fatta; Martina Micai; Maria Enrica Sali; Marina Bellomo; Tommaso Salvitti; Francesca Fulceri; Angela Castellano; Massimo Molteni; Giovanna Gambino; Manuel Posada; Giovanna Romano; et al. (Child and Adolescent Psychiatry and Mental Health, 2023)
Abstract Background This nationwide study aimed to estimate Autism Spectrum Disorder (ASD) prevalence in 7–9-year-old Italian children. Promoted by Italy's Ministry of Health and coordinated by the National Observatory for Autism at the National Institute of Health, it covered schools in northern (Lecco and Monza-Brianza), central (Rome and its province), and southern (Palermo and its province) regions from February 24, 2016, to February 23, 2018, using a multi-stage approach defined by the European Union's ASD network. Methods Phase one identified ASD-diagnosed children in mainstream schools through local Ministry of Education (MoE) disability registries. Phase two had a subset of schools screen 7–9-year-olds using the Social Communication Questionnaire-Life version (SCQ-L). Those with SCQ-L scores of 15 + underwent clinical consultation for ASD symptoms, cognitive abilities, and life skills. To counter potential false negatives, 20% scoring 11–14 were randomly assessed via Autism Diagnostic Interview-Revised (ADI-R). Results MoE data revealed 9.8 per 1000 certified ASD children in the north, 12.2 in the central, and 10.3 in the south. In phase two, 35,823 SCQ-L questionnaires were distributed across 198 schools (northern: 11,190 in 49 schools, central: 13,628 in 87 schools, southern: 11,005 in 62 schools). Of SCQ-L respondents, 2.4% (n = 390) scored above the 15 cutoff. Among these, 100 had ASD diagnoses, and 50 had other diagnoses. Among 115 families assessed, 16.5% (n = 19) received ASD diagnoses. Conclusions The estimated prevalence of ASD in Italy was 13.4 (11.3–16.0) per 1,000 children aged 7–9 years, with a male-to-female ratio of 4.4:1. It will guide national policies in enhancing services tailored to the specific needs of autistic children.